PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. REMCO RUBBER INDONESIA PALEMBANG - Gyronimo Rivaldo Fernand; Wani Fitriah; Lesi Agusria (Prodi Bisnis Digital Fakultas Ekonomi Dan Bisnis, 2025)
This study aims to (1) determine the influence of motivation and organizational culture on the performance of employees of PT. REMCO RUBBER INDONESIA PALEMBANG. This study used 70 samples. Sampling technique uses the Slovin formula. The data collection technique used is the questionnaire technique (questionnaire). The analysis techniques used are multiple linear regression analysis, f-test, t-test, and coefficient of determination. The results of the t-test of motivation variables and organizational culture have a positive effect on employee performance at PT. REMCO RUBBER INDONESIA PALEMBANG Analysis of the determination coefficient shows that there is an adjusted R square number of 0.389, meaning that the motivation variable, and the work environment are able to contribute to the increase in employee performance, with a contribution of 38.9%. This can be interpreted that employee performance can be explained by the variables of motivation and work discipline of 38.9%. While the rest is explained by other variables that are not included in this study.